Eroticism as the body without organs in Dennis Cooper's Frisk: grand narratives, desire, and infinity. Issue 4 (3rd April 2023) - Antonio Férez Mora, Pedro
ABSTRACT: This article argues that the portrayal of eroticism as a materialistic and process-based force in Dennis Cooper's Frisk (1991) corresponds with Deleuze and Guattari's concept of the BwO (Body without Organs). It is suggested that this articulation challenges heteronormative futurity-based conceptions of the temporal projection of sexuality while offering an alternative possibility (infinity) to the existing critical array of queer temporalities (the impossibility of the future and utopia). Contrary to the latter chronologies that locate the outcome of sexuality in an elusive and hypothetical no-time, this article asserts that infinity – articulated through the concept of the BwO – situates queer erotic time in the endless present that stems from the carnal depths of monads. Understanding eroticism as productive of infinity facilitates an onto-epistemologically constructive interpretation of Cooper's portrayal of sexual desire, which is uncommon in existing critical commentary. Finally, this article shows that, by establishing infinity as the temporality of eroticism, Cooper engages with a momentous strand of queer theory that seeks to articulate materialistic ways of looking at the temporal projections of sexuality.